Development and validation of UV-spectrophotometry method for quantitative determination of amorphous darunavir - M. A. Mandrik; I. A. Sadkovskii; E. D. Pinegina; L. A. Korol; I. I. Krasnuk (Разработка и регистрация лекарственных средств, 2024)
Introduction. Darunavir as an effective antiretroviral drug is widely used in clinical practice, including for the treatment of pediatric patients, as well as pregnant women, and for personalized therapy. Currently darunavir is used in the production of finished dosage forms, both in the form of crystalline ethanolate and in the form of an amorphous substance. In this regard, there is a need to develop and improve methods for the quantitative determination of darunavir. As an inexpensive and effective alternative to common chromatographic and titrimetric methods, spectrophotometric determination of darunavir in the ultraviolet region of the spectrum (UV spectrophotometry) may be used.Aim. To develop and validate a method for the quantitative determination of amorphous darunavir in the substance by UV spectrophotometry.Materials and methods. The following substances and consumables were used for the research: powdered amorphous darunavir substance (USP); darunavir reference standard (MSN Pharmachem Pvt. Ltd., India); methanol for HPLC Gradient Grade 99.9 % (High purity); acetonitrile for HPLC Gradient Grade 99.9 %; glacial acetic acid for HPLC; 0.1 M perchloric acid solution (in anhydrous acetic acid) for titration in non-aqueous media; nylon syringe filters with a pore diameter of 0.22 microns. Spectrophotometric determination of darunavir was carried out using an Cary 60 spectrophotometer (Agilent Technologies, USA) and a UNICO 2800 spectrophotometer (United Products & Instruments, Inc., USA). To prepare standard solutions, we used analytical balance Analytical Balance MS105/A (METTLER TOLEDO, Switzerland), analytical balance GH-120 (AND, Japan) class A measuring glassware, graduated pipettes ISOLAB.Results and discussion. The method was developed and validated for the following characteristics: specificity, linearity, accuracy, precision, analytical range. According to the study results, the main validation characteristics of the method meet the acceptance criteria.Conclusion. A new method for the quantitative determination of amorphous darunavir by UV spectrophotometry was successfully developed and validated. The method may be used to control the quality of substances of amorphous darunavir, including the intrapharmaceutical control.